PENINGKATAN PENGETAHUAN DAN KETRAMPILAN KONSELING MENYUSUI MELALUI PELATIHAN MENGGUNAKAN MEDIA DUKESI (MODUL PAKET ASI) - Ani, Murti; Astuti, Anjar; Harwijayanti, Bekti Putri; Ristiana, Ristiana (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
Breastfeeding is very beneficial for babies, mothers and families. However, not all mothers provide breastfeeding exclusively to their babies, because there are very limited breastfeeding counselors and the low availability of educational facilities and infrastructure on breastfeeding. The solution offered is to provide assistance and training to midwives who have not become breastfeeding counselors to be able to provide breastfeeding counseling using the Dukesi media (Breastfeeding Package Module). Dukesi is a module that makes it easier for mothers to get various information about breastfeeding. The training was attended by 26 midwives from 26 Primary Health Care in Blora District, conducted for 3 meetings. The first meeting was the pretest, delivering material on the role of health workers to increase exclusive breastfeeding coverage, use of health education media, material on the breastfeeding package module. The second meeting was providing material on breastfeeding counseling technique skills. The third meeting is the practice of breastfeeding counseling, posttest and evaluation. Based on the paired t-test, it was found that there was an effect of training using dukesi media on the knowledge level of 0.000 (<0.05) and there was an effect of training using dukesi media on breastfeeding counseling skills at 0.000 (<0.05).Â Keywords: breastfeeding; counseling; dukesi; module; training